2019
DOI: 10.3856/vol47-issue5-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding vegetable substrates on Penaeus vannamei pre grown in biofloc system on shrimp performance, water quality and biofloc composition

Abstract: The effect of adding vegetable substrates: wheat bran (WB), oat bran (OB) and amaranth seeds (AS) on water quality, biofloc composition and production response of Penaeus vannamei intensively pregrown, was evaluated during five weeks. Water quality parameters (temperature, pH, salinity and dissolved oxygen) were monitored twice a day; nitrogenous compounds (TAN, NO2-N, NO3-N) and the total suspended solids (TSS), were recorded weekly. Weight gain and survival of juveniles were monitored each week. Chemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…But, the use of carbon sources with complex structures decreased ammonia concentration when compared to molasses with simple structures. Abiri et al (2022) reported that fermenting complex carbon sources with probiotics decreases ammonia concentration than the non‐fermented carbon sources which indicate probiotics with external enzymes decomposed rice bran and corn starch resulting in low concentrations of ammonia and nitrite (Irfan et al, 2016; Peiro‐Alcantar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…But, the use of carbon sources with complex structures decreased ammonia concentration when compared to molasses with simple structures. Abiri et al (2022) reported that fermenting complex carbon sources with probiotics decreases ammonia concentration than the non‐fermented carbon sources which indicate probiotics with external enzymes decomposed rice bran and corn starch resulting in low concentrations of ammonia and nitrite (Irfan et al, 2016; Peiro‐Alcantar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, Arnesen found that the amount of oat bran had a significant effect on the weight gain in rainbow trout, with a maximum occurring when oat bran was 170 g/kg in the daily diet [ 14 ]. Peiro et al pointed out that supplementation with oat bran as a substrate had positive effects on the productive response of shrimp during their pregrowth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%